The Many Lives of James Milne Aitchison, Battle of Windsor Raider - Hundey, Ian (Ontario History, 2023)
James Milne Aitchison was a privileged child in rural Scotland, a troubled young man in Edinburgh, a failed immigrant in Upper Canada, a Patriot raider at the Battle of Windsor in December 1838, a Van Diemen’s Land (Tasmania) convict, and a colonist in what is now Victoria State, Australia. This article explores Aitchison’s many ‘lives’, drawing on fifty years of the author’s research-findings including material from the recent rescue of a cache of Aitchison documents from an abandoned house in Scotland.